INTERVENÇÃO NA PARADA CARDÍACA: PROPOSTA DE EDUCAÇÃO PERMANENTE COM PROFISSIONAIS DA EDUCAÇÃO INFANTIL - Santos Sousa , Jessyca; Santos Correa , Patricia; Santos Pereira , Fabrina; Costa de Sousa, Noemi; Santos Miranda, Carolina; Farias de Oliveira , Elenilda (Revista Formadores, 2023)
.